Trade unions and the impact of technological changes on the labour market (Economic and Political Thought, 2016)
The scientific and technological revolution, as well as rapid accelerationin business processes on a global scale, affect labour and capital in an asymmetricmanner. Capital is inherently more flexible than human beings, who,in addition to economic constraints, live in the network of social relations.The position of the working class is additionally weakened by process automation,replacing workers by increasingly intelligent robots. Our intentionis to sketch a sequence of cause and effect of these processes: describe thebasic aspects of the transformation of the labour market, their impact ontrade unions and outline the future outlook for the trade union movement.